1980
DOI: 10.2466/pms.1980.51.2.541
|View full text |Cite
|
Sign up to set email alerts
|

Memory Deficits in Depression: Evidence Utilizing the Wechsler Memory Scale

Abstract: The performance of 21 hospitalized depressed patients was compared to a matched group of 21 controls on the Wechaler Memory Scale. The depressed patients showed deficits on Mental Control, Verbal Learning, and Visual Reproduction tasks, which indicate impairment of memory functions in depression. There may be a deficit in the attention and alerting mechanism of depressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 5 publications
2
32
1
1
Order By: Relevance
“…Most studies consistently report no short-term memory deficits in depressed patients [74, 75, 84]assessed through the digit span task [73, 85], although this was not replicated by Breslow et al [76], who found shorter spans in forward and backward order. The apparent short-term memory impairment may reflect attentional dysfunction, which is similar to saying that difficulties in concentration may lead to greater distractability and interference effects [42].…”
Section: Neuropsychological Functions In Bipolar Disordermentioning
confidence: 91%
See 1 more Smart Citation
“…Most studies consistently report no short-term memory deficits in depressed patients [74, 75, 84]assessed through the digit span task [73, 85], although this was not replicated by Breslow et al [76], who found shorter spans in forward and backward order. The apparent short-term memory impairment may reflect attentional dysfunction, which is similar to saying that difficulties in concentration may lead to greater distractability and interference effects [42].…”
Section: Neuropsychological Functions In Bipolar Disordermentioning
confidence: 91%
“…Nevertheless, there are discrepancies among the investigators when the task used to evaluate long-term memory is the logical memory subtest of the Wechsler Memory Scale [73]. While some studies observed little or no impact of the depressed state on this task [74, 75], others disagree [76, 77]. Discrepancies in findings could be explained by different methods of assessment.…”
Section: Neuropsychological Functions In Bipolar Disordermentioning
confidence: 99%
“…However, the finding that PTSD-diagnosed veterans with comorbid depression did not differ from PTSD-diagnosed veterans without comorbid depression on key intellectual or cognitive variables suggests that group differences in cognitive and intellectual performance cannot be attributed exclusively to depression. Moreover, although attention deficits have been described in psychologically distressed samples (Breslow, Kocsis, & Belkin, 1980;Sackheim et al, 1992) and in affective disorders (cf. R. A.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have clinical depression frequently have impaired attention and STM, often secondary to vegetative signs (eg, poor sleep) and distraction associated with dysphoric preoccupation and obsessive thinking [70]. They do not adopt active, efficient encoding strategies [71], and they tend to put forth minimal effort, often giving up easily on tasks.…”
Section: Depressionmentioning
confidence: 99%